Encourage of Sustainable Business – Approaches for Increasing of the Scale and Impact Over Natural Tourism in Shumen Municipality - Yordanova, Diyana (Vilnius University Proceedings, 2025)
Many companies have made their reorganisation and optimisation of the resources led by two main reasons – lowering production costs and decreasing production pollution. In this period of transition, there are still new opportunities for clear, responsible and sustainable business using natural resources. As the technological world advances, people increasingly need tranquillity and to live in sync with nature. Sustainable business practices are crucial for the long-term success of natural tourism. By prioritizing environmental protection, social responsibility, and economic viability, businesses can ensure that tourism benefits both visitors and the destinations they explore. The subject of the article is the development of a new thermal spring complex in Marash, Shumen province, Bulgaria, as an opportunity for establishing a recognisable place for health and sustainability.
Keywords: sustainable business; nature tourism; circular economy; new opportunity; thermal pool